Leadership Orientation In Indian Small Businesses - Brinkman, John; Kallarakal, Tomy K. (Ushus Journal of Business Management, 2009)
The paper considers how leadership is practiced currently in SMEs situated in the Bangalore region of India. Thus addressing the lack of research into leadership-in-practice noted by a number of authors (Stogdill, 1974; Bryman, 1992; Gronn & Ribbins, 1996; Yukl, 2005) and hence the paper makes a contribution towards understanding of leadership within the Indian SME sector. The research focuses on the leader, not followers, and considers what leaders in SMEs do and would like to do. The research project is descriptive and aims to give a snapshot of current views on leadership by Indian SME leaders. This was achieved by use of a 33-item questionnaire and semi-structured joint interviews. The questionnaire was constructed to consider leadership behaviours based on the three-dimensional taxonomy proposed by Yukl et al. (2002). Here three metacategories (Task-Oriented Behaviours, Relations-Oriented Behaviours & Change-Oriented Behaviours) are categorised in line with the behaviours identified. This multidimensional model does not attempt to classify whether a leader is more focused on one area but to 'classify specific leadership behaviours' (Yukl, 2005).